2023
DOI: 10.1038/s41467-023-36459-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-protective antibodies against common endemic respiratory viruses

Abstract: Respiratory syncytial virus (RSV), human metapneumovirus (HMPV), and human parainfluenza virus types one (HPIV1) and three (HPIV3) can cause severe disease and death in immunocompromised patients, the elderly, and those with underlying lung disease. A protective monoclonal antibody exists for RSV, but clinical use is limited to high-risk infant populations. Hence, therapeutic options for these viruses in vulnerable patient populations are currently limited. Here, we present the discovery, in vitro characteriza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 89 publications
(113 reference statements)
1
5
0
Order By: Relevance
“…However, low-dose palivizumab offered limited protection, reducing viral loads by approximately 20-fold in the lungs and 4fold in nasal turbinates (Fig. 6a), echoing earlier ndings 33,48 . Pulmonary histopathology implied that h5B11 was more adept at curtailing pulmonary in ammation than nirsevimab, particularly in lessening alveolitis and interstitial pneumonitis (Fig.…”
Section: B11 Shows Potent Prophylactic E Cacy In the Rsvinfected Cott...supporting
confidence: 59%
See 3 more Smart Citations
“…However, low-dose palivizumab offered limited protection, reducing viral loads by approximately 20-fold in the lungs and 4fold in nasal turbinates (Fig. 6a), echoing earlier ndings 33,48 . Pulmonary histopathology implied that h5B11 was more adept at curtailing pulmonary in ammation than nirsevimab, particularly in lessening alveolitis and interstitial pneumonitis (Fig.…”
Section: B11 Shows Potent Prophylactic E Cacy In the Rsvinfected Cott...supporting
confidence: 59%
“…1e-h). Comparatively, nirsevimab, which has been proved display approximately 4-fold enhanced in vitro neutralizing activity over its precursor D25 against B18537 21,33,35,42 . We found that nirsevimab could effectively neutralize A2, Long and B9320, with comparable potencies (IC 50 : 1.79-4.61 ng/mL) to that of 5B11.…”
Section: B11 Is a Prefusion-speci C Potent And Broad Nabmentioning
confidence: 99%
See 2 more Smart Citations
“…While IgA bnAbs have been described for antigenically distinct viruses that infect mucosal surfaces such as HIV [ 83 , 107 ], SARS-CoV-2 [ 85 ], and common respiratory viruses [ 108 ], to our knowledge, F25.S02 is the first known IgA bnAb against flaviviruses. A recent study showed that infection by the malaria parasite, Plasmodium falciparum , another mosquito-borne pathogen, induces serum IgA production in humans that contribute to protection against disease [ 109 ].…”
Section: Discussionmentioning
confidence: 99%